Multiple Digestive Enzymes: Activity and Inactivation of Digestive Enzymes - Fukuchi, Hiroshi; Seki, Yoko; Yoshida, Minoru; Shintani, Hiromichi; Ikeda, Hiroaki; Kawakita, Yurie (Japanese Journal of Hospital Pharmacy, 1978)
The activity of α-amylase, glucoamylase, protease, lipase and cellulase contained in such commercial multiple digestive enzyme preparations as Aczym, Excelase, Politose and Toughmac-E capsule was determined. These digestive enzymes were immersed in citric acid solution with a pH of 2.0 for 5 minutes and the loss rate of enzyme activity due to acidic environment was determined. Each digestive enzyme had characteristic activity against each substrate. However, all the four preparations showed a 100% loss in glucoamylase activity, while the loss rate of α-amylase, protease, lipase and cellulase ranged from 30 to 76%. Therefore, multiple digestive enzyme preparations should be coated with materials suitable for each enzyme contained in view of changing pH in digestive tract.